Principales factores de riesgo de enfermedades fúngicas invasivas en trasplantados hematopoyéticos Hospital Nacional Edgardo Rebagliati Martins 2010 a 2014 - Reyna Vargas, Oscar Meliton (2020)
Objective: To determine the main risk factors for invasive fungal diseases in patients with hematological malignancies undergoing hematopoietic precursor transplantation of the Edgardo Rebagliati Martins National Hospital. Method: It is a case-control study, the sample was 25 cases and 104 controls. The selection was probabilistic. In the analysis bivariate and multivariate logistic regressions were used to measure association with Odds Ratio, with 95% confidence interval and p <0.05 with SPSS 25. Results: The mean age was 43 years and the basic neoplasms that mostly motivated the transplant were multiple myeloma, Hodgkin lymphoma and non-Hodgkin. The main factors associated with invasive fungal diseases were: mean days of hospitalization (p: 0.001), high-risk base hematologic malignancy (p: 0.000), history of invasive fungal disease (p: 0.033), type of hematopoietic precursor transplant (p: 0.000), grade III and IV mucositis (p: 0.001) and duration of neutropenia (p: 0.0001). Of these, prolonged duration of neutropenia (> 14 days) behaved as the main risk factor (p: 0.007; OR 22.45, 95% CI: 2.3-216), while hospitalization days greater than 33 days increased the risk in 7% (p: 0.001; OR: 1.07, 95% CI: 1.01-1.33). Conclusion: Neutropenia older than 14 days increases the risk of invasive fungal disease 22 times more, while hospitalization older than 33 days increases the risk 1.07 times more. It is suggested to carry out studies of greater power given the wide confidence intervals.